THE ROLE OF MIGRATION IN ENSURING PERSONNEL SECURITY OF THE STATE - E. Astakhova; N. Larionova; E. Krivokora; A. Kostina (Вестник Северо-Кавказского федерального университета)
The article presents the analysis of migration flows in the Russian Federation, determines their impact on the level ofpersonnel security of the state. The directions of state regulation of the labor market (reduction of tension, achievement of maximum employment, implementation of state programs, international cooperation), as well as factors that have a direct and indirect impact on the level ofpersonnel security of the state and the necessary conditions for its evaluation are outlined. The complex criterion of an estimation of level ofpersonnel safety of the state on the basis of coefficients ofweight and expert estimations is offered.